A proteomic approach reveals the variation in human platelet protein composition after storage at different temperatures. (3rd April 2019) - Wang, Shichun; Jiang, Tianlun; Fan, Yahan; Zhao, Shuming
Abstract: Cryopreservation can slow down the metabolism and decrease the risk of bacterial contamination. But, chilled platelets (PLTs) show a reduced period in circulation due to the rapid clearance by hepatic cells or spleen macrophages after transfusion. The deleterious changes that PLTs undergo are mainly considered the result of PLT protein variation. However, the basis for proteomic variation of stored PLTs remains poorly understood. Besides count, activation markers (CD62P and Annexin V), and aggregation, we used quantitative mass spectrometry to create the first comprehensive and quantitative human PLT proteome of samples stored at different temperatures (22°C, 10°C and −80°C). We found different conditions caused different platelet storage lesion (PSL). PLT count was decreased no matter at what temperature stored. PLTs viability at low temperature dropped by 21.78% and 11.21%, respectively, as compared 10.26% at room temperature, there were no significant differences between the storage methods. Membrane expression of CD62P gradually increased in all groups especially stored at 22°C up to 40% and 10°C up to 30%. However, exposure of PS on the PLT membrane was below 1% in every group. The PLT proteome showed there were 575 and 454 potential proteins identified by general iTRAQ analysis and phosphorylation iTRAQ a nalysis, respectively, among them, 33 common differentially expressed proteins caused by storage time and 44 caused by storage temperature Especially, membrane-bound proteins (such as FERMT3, STX4, MYL9 and TAGLN2) played key roles in PLT storage lesion. The pathways "Endocytosis", "Fc gamma R-mediated phagocytosis" and "Regulation of actin cytoskeleton" were affected predominantly by storage time. And the pathways "SNARE interactions in vesicular transport" and "Vasopressin-regulated water reabsorption" were affected by cold storage in our study. Proteomic results can help us to understand PLT biochemistry and physiology and thus unravel the mechanisms of PSL in time and space for more successful PLT transfusion therapy.